Thymine based copolymers: Feasible sensors for the detection of persistent organic pollutants in water - Ledesma, Julieta (2017)
Polycyclic Aromatic Hydrocarbons (PAHs) are among the main persistent organic pollutants in water, because they can cause serious diseases in living organisms. The PAHs trace levels in environmental samples makes their detection particularly difficult. The development of new fluorescence spectroscopic sensors is a realistic alternative for the quantification of PAHs at very low concentrations. Bio-inspired copolymers based on thymine and charged groups showed high affinity for benzo[a]pyrene, the nastiest contaminant of the PAHs group, and can be used to enhance their native luminescence. In the present work we rationalized the observed experimental evidence using a theoretical model that studies the plausible non-covalent interactions (polar hydrogen-π, π-π "stacking", etc.) between these compounds, in order to make a realistic design of new thymine-based copolymers sensors.